An Italian Neurorehabilitation Hospital Facing the SARS-CoV-2 Pandemic: Data From 1207 Patients and Workers - Salvia, Antonino; Morone, Giovanni; Iosa, Marco; Balice, Maria Pia; Paolucci, Stefano; Grasso, Maria Grazia; Traballesi, Marco; Nocentini, Ugo; Formisano, Rita; Molinari, Marco; Rossini, Angelo; Caltagirone, Carlo (Frontiers in Neurology, 2020)
The aim of the present observational study is to report on the data from a large sample of inpatients, clinical staff and other workers at an Italian neurorehabilitation hospital dealing with SARS-CoV-2 infections, in order to analyze how it might have affected the management and the effectiveness of neurorehabilitation. The data on infection monitoring, obtained by 2192 swabs, were reported and compared among 253 patients, 722 clinical professionals and 232 other hospital workers. The number of admissions and neurorehabilitation sessions performed in the period from March-May 2020 was compared with those of the same period in 2019. Four patients and three clinical professionals were positive for COVID-19 infection. Six out of these seven people were from the same ward. Several measures were taken to handle the infection, putting in place many restrictions, with a significant reduction in new admissions to the hospital (p<0.001). However, neither the amount of neurorehabilitation for inpatients (p=0.681) nor the effectiveness of treatments (p=0.464) were reduced when compared to the data from 2019. Our data show that the number of infections was contained in our hospital, probably thanks to the protocols adopted for reducing contagion and the environmental features of our wards. This allowed inpatients to continue to safely spend more than 3 hours per day in neurorehabilitation, effectively improving their independence in the activities of daily living.